Nano Sized Hydroxyapatite-Polylactic Acid-Vancomycin in Alleviation of Chronic Osteomyelitis - Lv XF; Zhou DM; Sun XH; Zhao Z (Dove Medical Press, 2022)
Xiao-Feng Lv,* Dong-Ming Zhou, Xiao-Hong Sun,* Ze Zhao Department of Trauma, First Affiliated Hospital of Baotou Medical College, Inner Mongolia University of Science and Technology, Baotou, Inner Mongolia Autonomous Region, 014010, People's Republic of China*These authors contributed equally to this workCorrespondence: Dong-Ming Zhou, Department of Trauma, First Affiliated Hospital of Baotou Medical College, Inner Mongolia University of Science and Technology, Baotou, Inner Mongolia Autonomous Region, 014010, People's Republic of China, Tel +86-13171243354, Email zhoudm2982@outlook.comBackground: Vancomycin (VAN) is effective in inhibiting inflammatory reactions in chronic osteomyelitis (CO), while nano-hydroxyapatite (nHA) can effectively address the poor biocompatibility and high brittleness of ordinary HA and better repair bone defects. Therefore, the efficacy of nHA combined with VAN for CO with bone defects deserves further discussion.Objective: To explore the effect of VAN, which is loaded in the nanodelivery system formed by nHA and polylactic acid (PLA), in CO therapy.Methods: The stability of nHA-PLA-VAN in PBS solution at different temperatures and its effect on VAN's half-life were determined in the physicochemical property test. Immunofluorescence (IF) determined the stability and permeability of Cy3-coupled nHA-PLA-VAN in bone marrow of B6/J mice. The cultured osteoblasts were further divided into control, polyethyleneimine (PEI), and nHA-PLA groups to observe their differences in cell proliferation, mineralization, and migration capacities. And a CO mouse model was constructed to detect the anti-CO effect of nHA-PLA-VAN.Results: nHA-PLA-VAN nanocomposites maintained good stability in different acidic solutions, favoring their long-term preservation in vitro. nHA-PLA extended VAN's half-life by 6-times. In the permeation test, nHA-PLA-VAN showed significantly higher permeation efficiency than PEI, enabling it to effectively transport VAN to bone marrow tissue, thus better inhibiting bacterial activity and reducing CD4, CD8, CD19, and CD20 expression in the lesion area of CO mice. In the osteoblast experiment, nHA-PLA more effectively maintained osteoblast viability and promoted proliferation and migration, thus better repairing defective bone tissue. In the CO mouse model, nHA-PLA-VAN better inhibited inflammatory reactions, such as congestion and edema in the focus, and increased the number and thickness of bone trabeculae. Furthermore, max load, elastic load, and rigidity coefficient of the bone defect area were recovered to a great extent.Conclusion: nHA-PLA-VAN may be a better choice for future treatment of CO.Keywords: nano-hydroxyapatite, polylactic acid, vancomycin, chronic osteomyelitis